The Effectiveness of The Implementation of The Gold Standard Project Based Learning Model to Increase The Digital Literacy Index of Teachers - Ahmad Swandi; Asdar Asdar; Susalti Nur Arsyad; Sri Rahmadhanningsih; Nurhayati Nurhayati (STKIP Singkawang, 2023)
One way to improve the quality of learning today is the use of various types of digital media in learning properly and correctly, which is known as school digitization. To support this program, it is necessary to carry out various activities for teachers to be able to improve their index and digital literacy skills. This study aims to find out how the index level and digital literacy skills of teachers after being given training and assistance with the Gold Standard Project Based Learning (GS-PjBL) model. The study was conducted on 20 teachers who participated in online and offline education and training activities. The research data was taken using two google form-based questionnaires, namely (i) a digital literacy index questionnaire, (ii) a digital literacy skills questionnaire given before and after training and mentoring activities. Based on the results of the analysis, there was an increase in the percentage of the digital literacy index before and after the activity which was marked by the Gain value. Based on the results of the analysis, the increase in the digital literacy index is in the medium and low categories. Therefore, the impact is seen that there is an increase in the index and literacy skills of the teacher group in Makassar City after participating in training and mentoring activities with the GS-PjBL model.